Thinking Critically through Storytelling Technique: Enhancing Students’ HOTS and English Speaking Skill - Kadek Trisna Kusuma Dewi (Journal of Educational Study, 2021)
This study aims to investigate the effectiveness of using storytelling technique in enhancing students’ critical thinking (HOTS) and English speaking skill in language learning. This study was designed by using library research method. This method is known as a method for collect data from various sources such as journal articles and books to write papers. The data was collected from several related literature reviews and which was qualitatively described. The finding showed that storytelling is to the use of storytelling shows that storytelling give positive effect on students’ in enhancing students’ speaking skills and make them think critically (HOTS). Therefore storytelling technique can be an effective’s solution for teacher in enhancing students’ critical thinking (HOTS) and their speaking skill in language learning.